A less invasive method of reducing the incidence of post-endoscopic retrograde cholangiopancreatography pancreatitis: Intravenous diclofenac sodium versus placebo - Chik I.A.N.; Jarmin R.; Ariffin A.; Othman H.; Zuhdi Z.; Azman A.; Mahmood N.R.K.N. (Innovare Academics Sciences Pvt. Ltd, 2024)
Indexed by Scopus